Development of visual function in early life stage mahi-mahi (coryphaena hippurus). Issue 5 (1st November 2020) - Magnuson, Jason T.; Stieglitz, John D.; Garza, Skylar A.; Benetti, Daniel D.; Grosell, Martin; Roberts, Aaron P.
ABSTRACT: Mahi-mahi ( Coryphaena hippurus ) are photopic predators that rely on vision for predator avoidance and foraging behavior. Research conducted on Mahi-mahi vision has been primarily focused on adults, with limited knowledge of the visual function and eye development in early life-stages. In this study, larval Mahi-mahi were obtained from spawning wild-caught broodstock and exposed to an optomotor response assay to assess visual function. Following behavioral assessment, histological examination was conducted on the retinal layers to determine changes in eye morphology and visual acuity early in development. There was an age-dependent increase in the ability of Mahi-mahi to exhibit an optomotor response at increasing speeds. Furthermore, this corresponded to an increase in retinal area and lens thickness between 7 and 10 day post-hatch (dph) larvae, where anatomical visual acuity (measured as the minimum separable angle) also improved. These findings help further the knowledge of visual development in early life-stage pelagic fishes.